Glycemic Improvement with Canagliflozin is Durable in T2DM Patients on Metformin - Kuznar, Wayne (MD Conference Express, 2013)
The sodium glucose cotransporter 2 inhibitor canagliflozin is associated with durable glycemic improvement over 104 weeks compared with glimepiride in patients with type 2 diabetes mellitus (T2DM) on background metformin therapy. Such was the primary finding of a Phase 3 randomized, double-blind efficacy and safety study.